Risk factors, prediction model, and prognosis analysis of myocardial injury after acute upper gastrointestinal bleeding - Hao, Junjun; Dang, Peizhu; Quan, Xingpu; Chen, Zexuan; Zhang, Guiyun; Liu, Hui; Shi, Tao; Yan, Yang (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiovascular complications in patients with acute upper gastrointestinal bleeding (AUGIB) have been associated with a high risk of subsequent adverse consequences. This study aimed to analyze the risk factors for myocardial injury in AUGIB patients, predict the risk of myocardial injury, and explore the clinical prognosis and influencing factors in AUGIB patients with myocardial injury. Methods: A retrospective case‒control study based on AUGIB patients in the First Affiliated Hospital of Xi’an Jiaotong University from 2016 to 2020 was performed. We divided the enrolled patients into a myocardial injury group and a control group according to whether they developed myocardial injury. The variables significant in the univariate analysis were subjected to binary logistic regression for risk factor analysis and were used to establish a nomogram for predicting myocardial injury. In addition, the logistic regression analysis was performed to better understand the risk factors for in-hospital mortality after myocardial injury. Results: Of the 989 AUGIB patients enrolled, 10.2% (101/989) developed myocardial injury. Logistic regression analysis showed that the strong predictors of myocardial injury were a history of hypertension (OR: 4.252, 95% CI: 1.149–15.730, P = 0.030), blood urea nitrogen (BUN) (OR: 1.159, 95% CI: 1.026–1.309, P = 0.018) and left ventricular ejection fraction (LVEF) < 68% (OR: 3.667, 95% CI: 1.085–12.398, P = 0.037). The patients with a tumor history (digestive system tumors and nondigestive system tumors) had no significant difference between the myocardial injury group and the control group (P = 0.246). A prognostic nomogram model was established based on these factors with an area under the receiver operator characteristic curve of 0.823 (95% CI 0.730-0.916). The patients with myocardial injury had a much higher in-hospital mortality rate (10.9% vs. 2.0%, P < 0.001), and an elevated D-dimer level was related to in-hospital mortality among the AUGIB patients with myocardial injury (OR: 1.273, 95% CI: 1.085–1.494, P = 0.003). Conclusion: A history of hypertension, renal dysfunction and cardiac insufficiency were the strong predictors of myocardial injury. Coagulopathy was found to be associated with poor prognosis in AUGIB patients with myocardial injury.